Dual antiplatelet therapy for reduction in mortality in patients with acute and chronic coronary syndromes - Lesiak, Maciej; Komosa, Anna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Dual antiplatelet therapy (DAPT) is a foundation of successful coronary artery disease management. DAPT is recommended according to ESC guidelines for 6 months following elective percutaneous coronary intervention and for 12 months following the acute coronary syndrome (ACS). ACS are the most cost-consuming type of the ischemic heart disease, which prominently requires hospital treatment. This risk significantly increases shortly after stopping DAPT, which is typical in most patients after 12 months following acute myocardial infarction (AMI). Therefore, one of the goals of long-term treatment of such patients should be the identification of those at increased risk of subsequent events, for whom prolonged DAPT will bring clinical benefits. It has been documented that prasugrel and ticagrelor, compared to clopidogrel, significantly reduce the incidence of major adverse cardiovascular events (MACE) in ACS patients. In addition to lowering composite ischemic endpoint, ticagrelor significantly reduced all-cause and cardiovascular mortality. The long-term use of ticagrelor in patients with a previous myocardial infarction was also related to a significant reduction in MACE. In patients who had a myocardial infarction 1–3 years earlier, the addition of ticagrelor to aspirin resulted in a substantial reduction in the composite endpoint of cardiovascular death, myocardial infarction, or stroke at the expense of a small but significant increase in bleedings. Hypothetical calculations have shown that replacing clopidogrel with ticagrelor in all patients with AMI in Poland would save more than three thousand lives within 12 months after AMI and more than a thousand within the following 2 years.